Pengaruh Penerapan Fishbone terhadap Efektivitas Pengambilan Keputusan di Perusahaan X - Cece Cece (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
Effective decision-making is a critical factor in achieving operational success within organizations. However, decisions made without proper root-cause analysis often fail to resolve problems thoroughly. This study aims to analyze the influence of the Fishbone Diagram application on decision-making effectiveness in Company X. The research employs a descriptive qualitative approach, using in-depth interviews, observations, and document analysis as data collection techniques. Informants include six employees directly involved in decision-making processes. The findings reveal that the implementation of the Fishbone Diagram improves problem identification accuracy, encourages cross-functional team participation, and results in more targeted and logical decisions. The diagram also enhances reflective thinking and cause-effect reasoning in formulating relevant solutions. Although technical limitations in applying the method were observed, overall, Fishbone demonstrates a positive impact on the quality and effectiveness of decision-making within the organization.